Tridimensional model of CBT: a transdiagnostic and transtheoretical pragmatic model - Kadir Özdel; Mehmet Hakan Turkcapar (Frontiers in Psychology)
Cognitive Behavioral Therapies (CBT) essentially represent an umbrella concept. Behavioral and cognitive (schema) theories form the foundation of all CBT approaches. However, the explanations and methods proposed by the models under the CBT umbrella sometimes contradict one another. We believe that a practical and pragmatic model integrating these CBT models will contribute significantly to the field. Upon reviewing the literature, we conclude that three individual strategies across three domains play a key role in the persistence of all psychopathologies: the attention/focus domain, the cognitive evaluation/operation domain, and the behavioral domain. Although individuals experiencing emotional difficulties utilize efforts in these three interrelated domains to solve their problems, these efforts often exacerbate the issues. The Tridimensional CBT (TriD-CBT) model recommends identifying the controllable components within these three domains and focusing interventions on them. In this article, we aim to present the general theoretical framework of the TriD-CBT model in light of the existing literature.